The solution of two-dimensional Fredholm integral equations of the first kind with multiprocessor systems - Vasilyev, M.P.; Yagola, A.G. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
Some aspects of solving two-dimensional nonlinear integral Fredholm equations of the first kind with multiprocessor systems are considered. Tikhonov’s regularization is applied to this ill-posed problem on the basis of minimization of Tikhonov’s functional by the conjugate gradient method. A number of schemes for parallelization are proposed. The efficiency of our approach is demonstrated.